THE USE OF TECHNOLOGY IN THE BNCC (BRAZILIAN NATIONAL CURRICULUM BASE) AND DIGITAL EXCLUSION IN PUBLIC EDUCATION: THE EDUCATIONAL ABYSS - Elaine Benetelli Geron, Regina (Revista Gênero e Interdisciplinaridade, 2025)
The objective of this work was to, through a bibliographic search, to approach the concept of digital inclusion and to analyze the difficulties found in the process of digital inclusion and the preparation and of students and teachers to face this new reality. The interest in the research theme, based on the difficulties encountered in times of pandemic and the wide open social differences that exist in Brazilian society, especially in education, in addition to the difficulties in accessing low-income students to the media available to continue the training processes that run through the literacy processes in all disciplines (mathematics and its technologies, languages ​​and its technologies and technology) which must also consider the senses mobilized from the insertion of the electronic network in textbooks, the manifestations of language at school, in all ways of producing meanings, especially those involving the use of new technologies.